Development Of A Web-Based Expert System For Healthy Diet Menu Recommendations Using The Certainty Factor Method - Despa Prasetyo Wardoyo; Fatma Sari Hutagalung (ISNU Sumatera Utara, 2025)
Diabetes mellitus and heart disease are two non-communicable diseases with a high prevalence rate in Indonesia. The increasing number of patients suffering from these diseases is influenced by unhealthy lifestyles, such as consuming foods high in sugar and fat, lack of physical activity, and low public awareness regarding healthy eating patterns. This condition causes many patients to experience difficulties in determining appropriate food menus according to their health conditions. Therefore, a system is needed to assist the community in determining healthy diet menus quickly, accurately, and practically. This study aims to design and develop a web-based expert system capable of providing healthy diet menu recommendations for patients with heart disease and diabetes using the Certainty Factor method. The research employed a quantitative method with data collection techniques including literature studies, observations, interviews, and library research. The system was developed using the PHP programming language and MySQL database. The Certainty Factor method was applied to calculate the level of confidence in food recommendations based on users’ health conditions such as blood pressure, blood sugar levels, cholesterol, body mass index, and family medical history. The results showed that the system was able to provide healthy food menu recommendations according to the user’s health condition with a certain level of confidence. This system is expected to help the public implement healthy lifestyles and serve as an initial consultation medium related to diet management based on information technology.